Reconsidering the Clinical Fellowship: Lessons From the 2025 Centers for Medicare & Medicaid Services Clarification for Speech-Language Pathology Services to Older Adults - Amber Heape (Perspectives of the ASHA Special Interest Groups, 2026)
The 2025 Centers for Medicare & Medicaid Services (CMS) clarification, which initially excluded clinical fellows (CFs) from the definition of a qualified speech-language pathologist, revealed broader issues in how the clinical fellowship aligns with contemporary licensure and health care systems. Although CMS later clarified that provisionally licensed CFs could bill under state law, the rapid shift in guidance resulted in uncertainty, hiring delays, and care disruptions for older adults in Medicare-funded settings. The CF, once created to ensure competence in an era without licensure, accreditation, or standardized exams, may now duplicate existing systems that already verify readiness for independent practice. The incident underscored a misalignment between American Speech-Language-Hearing Association certification requirements and federal regulatory frameworks, exposing how the CF can contribute to workforce delays, inequities in pay and mobility, and inconsistent mentorship that varies widely across settings. Taken together, these issues suggest that the CF may no longer align optimally with contemporary speech-language pathology practice, as examined through a structure–process–outcome framework. A structured postlicensure mentorship model may better support workforce readiness and promote stable access to services for older adults.